Analisis Penerimaan Sistem Informasi Akademik Santri Berbasis Web di Pondok Pesantren Al Halim Garut Menggunakan Metode Technology Acceptance Model - Akmala Hadita; Wufron Wufron; Yosep Septiana (Institut Teknologi Garut, 2023)
Pondok Pesantren Al Halim Garut is a non-formal educational institution with the aim of studying, interpreting, exploring, animating, and applying Islamic teachings by emphasizing the importance of religious ethics as a guideline for daily behavior. The Santri Academic Information System is needed to make it easier for parents of students and administrators of Islamic boarding schools to search for academic information for students at Islamic boarding schools. Because the Santri Academic Information System at the Al Halim Garut Islamic Boarding School has just been used, it is necessary to analyze the Santri Academic Information System Acceptance using the Technology Acceptance Model Method, to determine the measurement of influence between constructs as well as a benchmark for adapting user acceptance of the system used. In this study, data processing analysis uses Structural Equation Modeling through the tools of Statistical Product and Service Solution and Analysis of Moment Structures. This study resulted in the level of user acceptance of the Santri Academic Information System with a probability value of below 5%, namely 0.000 and the influence between the constructs of the Technology Acceptance Model with 3 accepted hypotheses, namely the variable perceived ease of influencing perceived usefulness, perceived usefulness affecting intention to use, and intention to use influencing use. real.